Reconfiguring Space - Thomas, Paul (VDM Verlag, 2009)
he starting point of my dissertation is the question: What would be needed of a device to culturally reconfigure the way that we see? The question has been addressed through a theoretical examination of spatial theories in modern times and a creative exploration of new spatialities in new media technologies, both visual and aural. Central to my thesis are three claims: 1. the paradigmatic mathematical theory of single-point perspective is fundamental to the imagining and construction of space in modern times; 2. perspective is a seductive space because its virtualisations seem more authentic than phenomenological experience; 3. the structure of perspective space prefigures the computer screen, hence any attempt to reconfigure the spatial imaginary through the devices of new media technologies must first confront the historical ubiquity of perspective. The specific focus of my written research is a comparative study of Filippo Brunelleschi's perspective device and the virtual reality work of Char Davies. This comparative study focuses on the ingredients of both devices as well as the similarities between the environments in which they were demonstrated. Brunelleschi's Peephole device, according to his biographer Manetti, first demonstrated perspective theory in the early fifteenth century. Brunelleschi's device, with its three main components, the mirror, the burnished silver and the painted panel, are examined in regards to the environment it was demonstrated in. The dissertation explores these elements as the essential conceptual ingredients for the reconfiguration of space in modern times. Aspects of Brunelleschi's device are also examined creatively in my practical work. Today emergent technologies are being used to explore the potential of a new spatial world order. However, these new technologies are generally based on an Old World order perspective. Even the cubist reconfiguration of space did not change, in any fundamental way, the dominant perspectival model of perception because it did not have the same ideological and psychological power as perspective, which seduced the viewer into believing that the gap (or loss) between the technology and reality had been compensated. Arguably, the same claims can be made for virtual reality devices. Hence, important to the dissertation is a comparative study of Brunelleschi's perspective device and the virtual reality work of Char Davies. The creative work investigates the effects and work of perspectival spatiality by examining (through digital video, photographically and sonically) residual spaces in the environment. To me these residual spaces provide potential resistances to the perspectival space from which they evolved, and thus show new ways of exploring the virtual reality of cyberspace that, while acknowledging the pervasive presence of perspective systems, also deconstruct or even map new post-perspective spatialities.